Charlemagne's relationship with the Umayyads of Andalusia (157-162 AH/774-778 AD ) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Andalus faced during the era of the emirate during the reign of 'Abd al-Rahman AIdakhl (138-172 AH / 756-788 AD) ,a number of risks and external challenges that targeted the security and civilization and therefore the Islamic presence which represents the most serious by: : The king Charlemagne crackdown on Al-Andalus years(157-162 AH/774-778 AD ), carried out at the request of the local rebel leaders Abdul Rahman inside, they had asked for help the king Charlemagne against prince Abdul Rahman without realizing the result of this action if it led to success, In addition to that most of these revolutions it was supported by the Abbasid caliphate but the campaign ended in dismal failure, and led the campaign for the results were negative for the king Charlemagne positive but it is positive for the prince of Al-Andalus Abdul Rahman.